UPAYA MENINGKATKAN LITERASI DAN MINAT BACA PADA ANAK-ANAK DESA PEMULUTAN ULU MELALUI KEGIATAN LES TAMBAHAN - Ananda, Putri Respa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Reading is one of the most important parts of learning. Through reading we can gain various knowledge that will help us achieve success in the future. This skill can be obtained outside the classroom. One of them is additional tutoring activities. This is a study that aims to determine the efforts made to increase children in Pemulutan Ulu Village's interest in literacy. Data from various sources were evaluated and discussed descriptively using the study or literature review method. The findings of this study show a steady increase as more information becomes available. However, it is not possible to claim that the modifications have increased interest in literacy. There are still many children who do not realize the importance of literacy. To overcome this, parents and educators need to provide more support. Reading will definitely broaden your horizons and give you better life choices. Reading different types of texts certainly provides many reading options that can enrich understanding and develop ways of thinking. The mindset is smarter and actively generates creative and innovative ideas.